Homobinuclear Complexes of Alkali metal salts of Organic Acids with Quinizarin - Prakash, D.; Alam, Mahfooz; Kumar, Birendra; Kumari Gupta, Anuj (Asian Journal of Chemistry, 2010)
Homobinuclear complexes of alkali metal salts of organic acids with quinizarin of type (ML)2 H2L', have been synthesised and charactrised by elemental analysis and infrared spectral data. Their infrared spectra suggest that the coordination of the ligand has taken place through hydroxy oxygen atom of the phenolic group as well as through oxygen atom of the quinone group. The lR spectra of the complexes also indicate the presence of hydrogen bond in them which is one of the dorninent factor for stability of the complexes.